Constraining the Age and Evolution of the Tuaheni Landslide Complex, Hikurangi Margin, New Zealand, Using Pore‐Water Geochemistry and Numerical Modeling. Issue 11 (1st June 2020) - Luo, Min; Torres, Marta E.; Kasten, Sabine; Mountjoy, Joshu J.
Abstract: The Tuaheni Landslide Complex (TLC) on the Hikurangi Margin is subject to reactivation, yet the timing of slide emplacement remains unknown. Here we modeled pore‐water data collected from the TLC during the International Ocean Discovery Program (IODP) Expedition 372 in 2017/2018 using a transient‐state reaction‐transport modeling approach. Our simulations reveal that the TLC was formed by two separate depositional events and that the most recent one occurred 12.5 ± 2.5 ka as a coherent ~40 m sediment block that carried its initial pore‐water signature. In addition, we show that the rapid burial of pore‐water SO4 2− in the pre‐slide sediments consumed an additional ~5.6 × 10 9 mole of CH4 over the entire Tuaheni South following the most recent depositional event. These findings provide significant insights into the nature and timing of the TLC and highlight the role of slope failure on subsurface methane cycling on millennial timescales. Plain Language Summary: One remarkable feature of the Tuaheni Landslide Complex (TLC) is the geomorphic signature of ongoing post‐slide deformation of the slide debris, analogous to slow‐moving terrestrial earthflows and rock glaciers. To reconstruct the temporal history of the TLC and evaluate its potential effect on subsurface methane cycling, we modeled the pore‐water data collected from the TLC using a nonsteady‐state model. We demonstrate that this landslide complex was formed by two separate depositional events and that the most recent one occurred 12.5 ± 2.5 ka as a coherent ~40 m sediment block. In addition, modeled response of the methane cycling rates to the slide mass emplacement shows that the rapid burial of pore‐water SO4 2− in the pre‐slide sediments into the newly developed methanic zone consumed an additional ~70 mol m −2 of CH4 over the 12.5 kyr that followed the most recent depositional event. This is the first study that provides the age constraint of the TLC and highlights the role of slope failure on subsurface methane cycling on millennial timescales. Key Points: The Tuaheni Landslide Complex was formed by two separate depositional events The most recent depositional event occurred 12.5 ± 2.5 ka as a coherent ~40 m sediment block Burial of sulfate in the pre‐slide sediments consumed an additional ~5.6 × 10 9  mol of methane over the entire Tuaheni South